2020
DOI: 10.3390/molecules25204709
|View full text |Cite
|
Sign up to set email alerts
|

LPS Induces GM-CSF Production by Breast Cancer MDA-MB-231 Cells via Long-Chain Acyl-CoA Synthetase 1

Abstract: Granulocyte–macrophage colony-stimulating factor (GM-CSF) is a monomeric glycoprotein that has been implicated in the tumor growth and progression of different types of cancer. GM-CSF is produced by various non-immune cells including MDA-MB-231 in response to various stimuli. However, the role of lipopolysaccharide (LPS) in the regulation of GM-CSF in MDA-MB-231 breast cancer cells so far remains unclear. Herein, we asked whether LPS could induce GM-CSF production in MDA-MB-231 cells, and if so, which signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The data showed that the inhibition of MAPK and NF- κ B suppressed the synergistic effect of acetate/TNFα on the production of MCP-1. Moreover, long-chain acyl-CoA has been shown to induce inflammation through MAPK/NF-κB activation [ 19 , 26 , 27 ]. Therefore, we determined whether ACSL1 had an impact on the acetate/TNFα-mediated phosphorylation of JNK, P38, ERK, and NF-κB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data showed that the inhibition of MAPK and NF- κ B suppressed the synergistic effect of acetate/TNFα on the production of MCP-1. Moreover, long-chain acyl-CoA has been shown to induce inflammation through MAPK/NF-κB activation [ 19 , 26 , 27 ]. Therefore, we determined whether ACSL1 had an impact on the acetate/TNFα-mediated phosphorylation of JNK, P38, ERK, and NF-κB.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting ACSL1 in monocytes suppressed the TNF-α-induced expression of CD11c, which is a highly expressed inflammatory marker on monocytes and macrophages during conditions of obesity [ 19 ]. ACSL1 regulates the TNFα- and LPS-induced GM-CSF production in breast cancer MDA-MB-231 cells [ 26 , 27 ], suggesting the role of ACSL1 in the regulation of growth-modulating cytokines or embryokines. Increased ACSL1 expression was detected in inflammatory macrophages from obese mice and humans [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted using RNeasy Mini Kit (Qiagen, Valencia, CA, USA) per the manufacturer’s instructions. cDNA was synthesized from 1 μg of total RNA using high-capacity cDNA Reverse Transcription Kits (Applied Biosystems, Foster City, CA, USA) [ 17 , 18 ]. Quantitative real-time PCR (qRT-PCR) was performed on a 7500 Fast Real-Time PCR System (Applied Biosystems) using TaqMan ® Gene Expression Master Mix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…After laser excitation of the samples, optimized emission-detection bandwidths were configured using Zeiss Zen 2012 control software (version 1.1.1.2.0, Gottingen, Germany). Subsequently, confocal images were captured, and fluorescence was measured using Zeiss Zen 2012 software (Gottingen, Germany) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%